Anti–SARS‐CoV‐2 Repurposing Drug Database: Clinical Pharmacology Considerations. (1st August 2021) - Zhang, Xinyuan; Yang, Yuching; Grimstein, Manuela; Liu, Guansheng; Kitabi, Eliford; Fan, Jianghong; Wang, Ying‐Hong; Earp, Justin; Weaver, James L.; Zhu, Hao; Liu, Jiang; Reynolds, Kellie S.; et al.
Abstract: A critical step to evaluate the potential in vivo antiviral activity of a drug is to connect the in vivo exposure to its in vitro antiviral activity. The Anti–SARS‐CoV‐2 Repurposing Drug Database is a database that includes both in vitro anti–SARS‐CoV‐2 activity and in vivo pharmacokinetic data to facilitate the extrapolation from in vitro antiviral activity to potential in vivo antiviral activity for a large set of drugs/compounds. In addition to serving as a data source for in vitro anti–SARS‐CoV‐2 activity and in vivo pharmacokinetic information, the database is also a calculation tool that can be used to compare the in vitro antiviral activity with in vivo drug exposure to identify potential anti–SARS‐CoV‐2 drugs. Continuous development and expansion are feasible with the public availability of this database.